Retraction notice to “Systematic green synthesis of silver oxide nanoparticles for antimicrobial activity” [Environ. Res. 202 (2021) 111627] - M. Mani; R. Harikrishnan; P. Purushothaman; S. Pavithra; P. Rajkumar; S. Kumaresan; Dunia A. Al Farraj; Mohamed Soliman Elshikh; Balamuralikrishnan Balasubramanian; K. Kaviyarasu (Environmental Research, 2026)

Curcumin nanoformulations for modulating neuroinflammation and oxidative stress in Alzheimer’s disease: blood–brain barrier transport, formulation strategies and therapeutic applications - M. Yasmin Begum; Manickam Rajkumar; Prabha Govindaraj; Nadarajan Prathap; Parappurath Narayanan Sudha; Mona Al Hamod; Hamoud Alotaibi; Deenathayalan Uvarajan (Inflammopharmacology, 2026)

Phytofabrication of Chitosan–MgO nanocomposites: Evaluation of their antioxidant, antibacterial, anticancer, and zebrafish embryo biocompatibility properties - M. Yasmin Begum; Manickam Rajkumar; Prabha Govindaraj; Krishnan Meenambigai; Mona Alhamod; Hamoud Alotaibi (Journal of Photochemistry and Photobiology B: Biology, 2026)

Promoting sustainable pest management through digital decision support tools: Insights from India - Justice A. Tambo; Malvika Chaudhary; Idah Mugambi; Madhu Manjari; Mahesh H. Munireddappa; Kritika Khanna; J.V. Mohan Rao; M. Bheemanna; Prabhuraj Aralimarad; Rajkumar Ramasamy (Agricultural Systems, 2026)

Integrated in silico docking, ADMET, and network pharmacology evaluation of Althaea officinalis L. phytocompounds targeting Park2 for the management of Parkinson’s disease - M. Heshetha; Muthineni Haneesh; Venkatesan Karthick; Rajkumar Thamarai; Singamoorthy Amalraj (Inflammopharmacology, 2026)

Long-term Conservation Agriculture with Subsurface Nitrogen Placement Enhances Wheat yield, Soil Nitrogen retention, and Nitrogen Use Efficiency in the North-west Indo-Gangetic Plains - Kiranmoy Patra; C. M. Parihar; Ayan Sarkar; K. Srikanth Reddy; D. R. Sena; Rajkumar Dhakar; Sneha Bharadwaj; Alok Sinha; Susnigdha Sengupta; Manojit Chowdhury; Hüdaverdi Gürkan; Hari Sankar Nayak (International Journal of Plant Production, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Demystifying the association of the gut–TMAO–heart axis: focusing on gut microbiota in myocardial infarction - Krushna Ch Maharana; Mayuri Adsule; M Rajkumar; Gopal Vishwas; Sanjiv Singh (Next Research, 2026)

MOF derived ZnO nanostructures modified with CoW12-polyoxometalates for enhanced sunlight driven degradation of methylene blue, ofloxacin and their mixtures - Nitin A. Tupsamindar; Arun S. Chopade; Sagar A. Chaudhari; Abhijit N. Kadam; Sandip R. Sabale; Vaishali Patil; Mohaseen S. Tamboli; Raisuddin Ali; Nguyen Tam Nguyen Truong; Vashishtha M. Gurame; Dattakumar S. Mhamane; Vijaykumar P. Ubale; et al. (Journal of Water Process Engineering, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Biogenic synthesis of CuO-TiO2 nanocomposites from Senna auriculata (L.) Roxb. Plant extract and its evaluation of antioxidant, antibacterial and anticancer activity of HepG2 cell lines - Manickam Rajkumar; S.I. Davis Presley; M. Yasmin Begum; Ali Alamri; Adel Al Fatease; Koyeli Girigoswami; Prabha Govindaraj; Shobana Sampath; Rajaram Madhankumar; Paramasivam Deepak (Biocatalysis and Agricultural Biotechnology, 2025)

Enhanced dual removal of chromium and lead ions from water using biopolymer modified ferric–alumina layered double hydroxides - V. Nithya Priya; D. Karthigaimuthu; S.Sasi Florence; M. Rajkumar; S.P.Linto Sibi; M.S. Sobana; J. Mobika; V. Vijayalakshmi; P. Ahila (Journal of Environmental Chemical Engineering, 2025)

Behaviour of prestressed hollow core slabs after exposure to elevated temperatures: an experimental and numerical approach - T M Jeyashree; P R Kannan Rajkumar (Innovative Infrastructure Solutions, 2025)

Resistance mechanism of energy canes developed from Saccharum spontaenum and Erianthus arundinaceus against sugarcane borer pests - M. Punithavalli; P. Govindaraj; M. Balaji Rajkumar (Journal of Asia-Pacific Entomology, 2025)

First record of fruit rot in soursop caused by Lasiodiplodia theobromae in India - Prathibha V. H.; Panjavarnam G.; Daliyamol; Rajkumar; Keerthana S.; Thejasri K. P.; Gangaraj K. P.; Rajesh M. K.; Vinayaka Hegde (Journal of Plant Pathology, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Production of biologically active recombinant salmon calcitonin in Escherichia coli and fish cell line - A. Nafeez Ahmed; S. Abdul Majeed; G. Taju; S. Suryakodi; S. Mithra; M. J. Abdul Wazith; K. Kanimozhi; V. Rajkumar; A. Badhusha; A. S. Sahul Hameed (Archives of Microbiology, 2025)

Sustainable selenium ions adsorption of cyclodextrin and cellulose functionalized layered double hydroxide/reduced graphene oxide nanocomposites - V. Nithya Priya; M. Rajkumar; V. Rajendran; J. Mobika; S.P. Linto Sibi; B. Veena; V. Vijayalakshmi; P. Ahila (Journal of Water Process Engineering, 2025)

The qualitative and molecular categorization for genetic diversity in Withania somnifera (L.) Dunal - S. Venugopal; M. Padma; M. Rajkumar; N. Seenivasan; P. Saidaiah; G. Sathish; A.C. Jnanesha; R.S. Kumar; R.K. Lal (Ecological Genetics and Genomics, 2024)

Seasonal variability of microplastic contamination in marine fishes of the state of Gujarat, India - Yagnesh B. Motivarash; Ashishkumar J. Bhatt; Rahul R. Jaiswar; Rehanavaz A. Makrani; Rajkumar M. Dabhi (Environmental Science and Pollution Research, 2024)

Euwallacea perbrevis (Schedl, 1951) and associated novel fungal symbiont, Fusarium sp.: A potential cause of wilting in cocoa, Theobroma cacao in India - Shivaji Hausrao Thube; R Thava Prakasa Pandian; M. Rajkumar; Merin Babu; A. Josephrajkumar; Santhoshkumar P; B.J. Nirmal Kumar; Vinayaka Hegde; Balanagouda Patil; H. Rajashekara; T. Prabhulinga; Babasaheb B. Fand; et al. (Crop Protection, 2024)

DeepNNet 15 for the prediction of biological waste to energy conversion and nutrient level detection in treated sewage water - T. Sathish; A. Vijayalakshmi; Raviteja Surakasi; N. Ahalya; M. Rajkumar; R. Saravanan; Sumarlin Shangdiar; Thandiwe Sithole; Kassian T.T. Amesho (Process Safety and Environmental Protection, 2024)

Insights into the population dynamics of phytophthora species associated with arecanut fruit rot disease - V.H. Prathibha; Balanagouda Patil; M.K. Rajesh; Sunil S Gangurde; M.N. Maruthi; K.P. Gangaraj; Thava Prakasa Pandian R; Daliyamol; M. Chaithra; Rajkumar; Vinayaka Hegde (Physiological and Molecular Plant Pathology, 2024)

Zinc solubilization and organic acid production by the entomopathogenic fungus, Metarhizium pingshaense sheds light on its key ecological role in the environment - C.M. Senthil Kumar; Sharon D'Silva; R. Praveena; Anees Kaprakkaden; L.R. Athira Krishnan; M. Balaji Rajkumar; V. Srinivasan; R. Dinesh (Science of The Total Environment, 2024)

Development and characterization of brain cell line from Trachinotus blochii and its application in virological and gene expression studies - A. Nafeez Ahmed; S. Mithra; S. Suryakodi; G. Taju; M. J. Abdul Wazith; K. Kanimozhi; V. Rajkumar; A. Badhusha; S. Abdul Majeed; A. S. Sahul Hameed (Journal of Fish Diseases, 2024)
A permanent cell line, SPB (Snubnose pompano brain) was established from Trachinotus blochii by the explant culture method. It has been sub‐cultured more than 75 passages and showed optimal growth at 28°C using L‐15 medium supplemented with 15% to 20% FBS. The SPB cells were cryopreserved at different passage levels for various applications. SPB cells were composed of fibroblastic and epithelial‐like cells. The SPB cells were tested for mycoplasma contamination which was found to be negative. The origin of the SPB cell line from T. blochii was confirmed by amplification of the mitochondrial cytochrome oxidase I (COI) gene. The transfection efficiency of SPB cell line is 15% assessed by expression of green fluorescent protein using pEGFP‐N1 plasmid. In addition, two CMV promotor plasmids pFNCPE42‐DNA and pcDNAVP28 were transfected to SPB cells and it shows high expression levels of FNCP of fish nodavirus and VP28 protein of white spot syndrome virus by immunostaining. The SPB cells showed susceptibility to SJNNV and the infection was confirmed by RT‐PCR, Western blot, ELISA, TCID 50 and RT‐qPCR. Experimental infection was carried out in T. blochii using SJNNV propagated in SPB cell line and found 100% mortality with clinical signs. The infection was confirmed by RT‐PCR. The SPB cell line can be used for propagation of fish viral pathogens and production of the recombinant proteins.

A comparative study on targeted gene expression in zebrafish and its gill cell line exposed to chlorpyrifos - Abdul Wazith M. J.; Taju G.; Abdul Majeed S.; Mithra S.; Nafeez Ahmed A.; Badhusha A.; Rajkumar V.; Sahul Hameed A. S. (In Vitro Cellular & Developmental Biology - Animal, 2024)

Effect of Pulsed Light Treatment for the Preservation of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; R. Pandiselvam; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; P. Preetha (Sugar Tech, 2024)

In vitro double haploid production through anther culture in niger (Guizotia abyssinica L.F. Cass) - Shrinkhla Maurya; Bhumika Sharma; Kajal Thakur; Suman Rawte; Nirmala Bharti Patel; Rajani Bisen; S. Rajkumar; Zenu Jha; M. Sujatha (In Vitro Cellular & Developmental Biology - Plant, 2024)

Humidity activated ultra-selective room temperature gas sensor based on W doped MoS2/RGO composites for trace level ammonia detection - S.P. Linto Sibi; M. Rajkumar; Mathankumar Manoharan; J. Mobika; V. Nithya Priya; R.T. Rajendra Kumar (Analytica Chimica Acta, 2024)

Advances in drying techniques for retention of antioxidants in agro produces - V. A. Athira; E. Gokulvel; A. M. Nandhu Lal; V. V. Venugopalan; Rajkumar; T. Venkatesh (Critical Reviews in Food Science and Nutrition, 2023)

Reproductive biology of green tiger shrimp Penaeus semisulcatus De Haan, 1844 in Palk Bay, southeast coast of India - M. Rajkumar; S. Lakshmi Pillai; P. Rameshkumar; R. Saravanan; S. Thirumalaiselvan; Josileen Jose; K.S. Sobhana; M. Rosalind George (Regional Studies in Marine Science, 2023)

Exploring the synergistic potential of higher alcohols and biodiesel in blended and dual fuel combustion modes in diesel engines: A comprehensive review - M. Gowthama Krishnan; Sundararajan Rajkumar; Jeyaseelan Thangaraja; Yuvarajan Devarajan (Sustainable Chemistry and Pharmacy, 2023)

Improvement in electrical energy efficiency of solar photovoltaic panel by passive refrigeration cooling system - M. Chandrasekar; S. Rajkumar; M. Varatharajulu (International Journal of Energy and Water Resources, 2023)

Identifying optimum residue levels for stable crop and water productivity and carbon sequestration under a conservation agriculture based rice-wheat system - Ram Swaroop Bana; Shanti Devi Bamboriya; Vipin Kumar; Samarth Godara; Donald S. Gaydon; Alison M. Laing; Rajkumar Dhakar; Y.S. Shivay; Vijay Singh Meena; Deepak Singh (Soil and Tillage Research, 2023)

Evaluation of Effect of Tapping Frequency and Lime Coating on the Biochemical Changes and Fermentation Rate of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; R. Pandiselvam (Sugar Tech, 2023)

Effect of packaging materials and storage temperature on the physicochemical and microbial properties of ultrasonicated mature coconut water during storage - Anjitha Jacob; I.P. Sudagar; R. Pandiselvam; P. Rajkumar; M. Rajavel (Food Control, 2023)

A Nationwide Analysis of Aneurysmal Subarachnoid Hemorrhage Mortality, Complications, and Health Economics in the USA - Lefko T. Charalambous; Syed M. Adil; Shashank Rajkumar; Robert Gramer; Elayna Kirsch; Beiyu Liu; Ali Zomorodi; Mark McClellan; Shivanand P. Lad (Translational Stroke Research, 2023)

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

Geological evolution of the Proterozoic Betul belt (∼2.16–0.95 Ga) of the Central Indian tectonic Zone: Its linkage to the assembly and dispersal of Columbia and Rodinia supercontinents - M. Lachhana Dora; Tushar Meshram; Srinivasa Rao Baswani; Vivek P Malviya; Dewashish Upadhyay; Mohd Shareef; Mohd Atif Raza; Sameer Ranjan; Rajkumar Meshram; Monaj Kumar Patnaik; Kirtikumar Randive (Gondwana Research, 2023)

Federated Analysis in COINSTAC Reveals Functional Network Connectivity and Spectral Links to Smoking and Alcohol Consumption in Nearly 2,000 Adolescent Brains - Harshvardhan Gazula; Kelly Rootes-Murdy; Bharath Holla; Sunitha Basodi; Zuo Zhang; Eric Verner; Ross Kelly; Pratima Murthy; Amit Chakrabarti; Debasish Basu; Subodh Bhagyalakshmi Nanjayya; Rajkumar Lenin Singh; et al. (Neuroinformatics, 2023)

Electronic sensitization enhanced p-type ammonia gas sensing of zinc doped MoS2/RGO composites - S.P. Linto Sibi; M. Rajkumar; Kamaraj Govindharaj; J. Mobika; V. Nithya Priya; R.T. Rajendra Kumar (Analytica Chimica Acta, 2023)

Constructing Z-scheme g-C3N4/TiO2 heterostructure for promoting degradation of the hazardous dye pollutants - M. Vijayan; Velu Manikandan; Chellakannu Rajkumar; Ashraf Atef Hatamleh; Bassam Khalid Alnafisi; G. Easwaran; Xinghui Liu; K. Sivakumar; Haekyoung Kim (Chemosphere, 2023)

Developing a numerical model to analyze the production process of PMEDM - G. Rajkumar; M. Saravanan; P. Marimuthu (Resources Policy, 2023)

Effect of mineral admixtures on mechanical and thermal properties of geopolymer mortar at elevated temperature - J. Baskara Sundararaj; P. R. Kannan Rajkumar; M. Sivasakthi; M. Jegan (Innovative Infrastructure Solutions, 2022)

Economic feasibility of subsurface drainage (SSD) to control waterlogging and soil salinity under different scenarios in the Tungabhadra project command, Karnataka, India - Karegoudar A V; Vishwanath J; Rajkumar R H; Anand S R; Polisgowdar B S; Ayyanagowdar M S; Nemichandrapp M; Kaledhonkar M J (Irrigation and Drainage, 2022)
The Tungabhadra irrigation command area (TBP) in Karnataka, India, has three scenarios: the head, mid and tail reach command areas. The head reach has ample good quality canal water availability, and the mid reach area has limited canal water availability. In recent decades, rice–rice monocropping in vertisols, especially by these head and mid reach farmers, has led to not only water shortages but also the development of waterlogging and secondary soil salinization in the tail (lower) reach of the command due to seepage. As the soil salinity in the head reach was less severe, a slightly wider drain spacing of 60 m was adopted over 15 ha. In the case of the mid reach, salinity was slightly higher than the head reach but slightly less than the tail reach, hence 50 m drain spacing was laid out over 24 ha. Due to the slightly higher soil salinity at the tail end of the command, a closer drain spacing of 40 m was adopted over 11 ha. In all these scenarios, the drain depth was 1.0 m. Despite differences in irrigation water availability and different soil salinity conditions, the study clearly indicated over six seasons that the SSD system is a viable solution for the reclamation of waterlogged saline soils and enhancing rice productivity in all three scenarios of the TBP command.

Correction to: Biology, morphology and molecular characterization of Rhaphipodus subopacus (Coleoptera: Cerambycidae): a new pest of cocoa (Theobroma cacao Linnaus) - Shivaji Hausrao Thube; Sangamesh Hiremath; R. Thava Prakasa Pandian; A. Josephrajkumar; Dnyaneshwar M. Firake; M. Rajkumar; Vinayaka Hegde (Applied Entomology and Zoology, 2022)

Biology, morphology and molecular characterization of Rhaphipodus subopacus (Coleoptera: Cerambycidae): a new pest of cocoa (Theobroma cacao Linnaus) - Shivaji Hausrao Thube; Sangamesh Hiremath; R. Thava Prakasa Pandian; A. Josephrajkumar; Dnyaneshwar M. Firake; M. Rajkumar; Vinayaka Hegde (Applied Entomology and Zoology, 2022)

First record of Fusarium falciforme (FSSC 3 + 4) a relevant human pathogen causing root decay of arecanut, Areca catechu L - R. Thava Prakasa Pandian; Shivaji Hausrao Thube; Babu Merin; V. H. Pratibha; M. Rajkumar; Priyank Hanuman Mhatre; Vinayaka Hegde (Journal of Plant Diseases and Protection, 2022)

In-Silico Design of a Novel Tridecapeptide Targeting Spike Protein of SARS-CoV-2 Variants of Concern - Sajjan Rajpoot; Kundan Solanki; Ashutosh Kumar; Kam Y. J. Zhang; Soni Savai Pullamsetti; Rajkumar Savai; Syed M. Faisal; Qiuwei Pan; Mirza S. Baig (International Journal of Peptide Research and Therapeutics, 2022)

Temporal trends in frost occurrence and their prediction models using multivariate statistical techniques for two diverse locations of Northern India - Santanu Kumar Bal; Rajkumar Dhakar; P. Vijaya Kumar; Adita Mishra; V. P. Pramod; M. A. Sarath Chandran; V. M. Sandeep; A. V. M. Subba Rao; K. K. Gill; Rajendra Prasad (Theoretical and Applied Climatology, 2021)

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Bioethanol production from seagrass waste, through fermentation process using cellulase enzyme isolated from marine actinobacteria - J. Rajkumar; E. Dilipan; M. Ramachandran; A. Panneerselvam; N. Thajuddin (Vegetos, 2021)

Quantification of greenhouse gas emissions from managed biofuel plantations in a semi-arid landscape of Southern India - G. R. Rao; P. Sathi Reddy; M. Rajkumar (Tropical Ecology, 2021)

Backyard poultry farming for sustained production and enhanced nutritional and livelihood security with special reference to India: a review - U. Rajkumar; S. V. Rama Rao; M. V. L. N. Raju; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

Water deficit-induced oxidative stress and differential response in antioxidant enzymes of tolerant and susceptible tea cultivars under field condition - M. Nalina; S. Saroja; M. Chakravarthi; R. Rajkumar; B. Radhakrishnan; K. N. Chandrashekara (Acta Physiologiae Plantarum, 2021)

A novel leaf rust resistance gene introgressed from Aegilops markgrafii maps on chromosome arm 2AS of wheat - K. Rani; B. R. Raghu; S. K. Jha; Priyanka Agarwal; Niharika Mallick; M. Niranjana; J. B. Sharma; A. K. Singh; N. K. Sharma; S. Rajkumar; S. M. S. Tomar; Vinod (Theoretical and Applied Genetics, 2020)

Morphological characterization and analysis of genetic diversity and population structure in Citrus × jambhiri Lush. using SSR markers - M. R. Rohini; M. Sankaran; S. Rajkumar; K. Prakash; A. Gaikwad; R. Chaudhury; S. K. Malik (Genetic Resources and Crop Evolution, 2020)

Tumor-derived exosomes in the regulation of macrophage polarization - Mirza S. Baig; Anjali Roy; Sajjan Rajpoot; Dongfang Liu; Rajkumar Savai; Sreeparna Banerjee; Manabu Kawada; Syed M. Faisal; Rohit Saluja; Uzma Saqib; Tomokazu Ohishi; Kishore K. Wary (Inflammation Research, 2020)

Novel thiazolinyl-picolinamide based palladium(II) complex-impregnated urinary catheters quench the virulence and disintegrate the biofilms of uropathogens - Deeksha Rajkumar; Durairajan Rubini; M. Sudharsan; D. Suresh; Paramasivam Nithyanand (Biofouling, 2020)

Evaluation of heavy metal contamination in soil using geochemical indexing approaches and chemometric techniques - H. Rajkumar; P. K. Naik; M. S. Rishi (International Journal of Environmental Science and Technology, 2019)

Evaluation of the Neuroprotective Effect of Sirt3 in Experimental Stroke - Rajkumar Verma; Rodney M. Ritzel; Joshua Crapser; Brett D. Friedler; Louise D. McCullough (Translational Stroke Research, 2019)

Effect of supplementing germinated sprouts of pulses on performance, carcass variables, immune and oxidative stress indicators in broiler chickens reared during tropical summer season - S. V. Rama Rao; B. Prakash; U. Rajkumar; M. V. L. N. Raju; T. Srilatha; E. P. K. Reddy (Tropical Animal Health and Production, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Marker-assisted introgression of opaque2 allele for rapid conversion of elite hybrids into quality protein maize - Firoz Hossain; Vignesh Muthusamy; Neha Pandey; Ashish K. Vishwakarma; Aanchal Baveja; Rajkumar U. Zunjare; Nepolean Thirunavukkarasu; Supradip Saha; Kanchikeri M. Manjaiah; Boddupalli M. Prasanna; Hari S. Gupta (Journal of Genetics, 2018)

Neoplasia in goldlined seabream, Rhabdosargus sarba (Forsskål, 1775) - V Singaravel; A Gopalakrishnan; K Raja; M Rajkumar; H W Ferguson (Journal of Fish Diseases, 2018)

Probabilistic assessment of phenophase-wise agricultural drought risk under different sowing windows: a case study with rainfed soybean - Rajkumar Dhakar; M. A. Sarath Chandran; Shivani Nagar; V. Visha Kumari (Environmental Monitoring and Assessment, 2017)

Distribution of recombinant VP28 protein in tissues and its immunomodulatory effect against white spot syndrome virus in whiteleg shrimp, Litopenaeus vannamei (Boone, 1931) - G. Taju; N. Madan; S. Abdul Majeed; T. Rajkumar; M. A. Farook; S. Vimal; A. Nazeer Basha; A. S. Sahul Hameed (Aquaculture International, 2017)

Protein Sparing Effect of Dietary Rumen Protected Lysine Plus Methionine in Growing Murrah Buffaloes (Bubalus bubalis) - Rajkumar Gami; S. S. Thakur; M. S. Mahesh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Alleviation of environmental stress in plants: The role of beneficial Pseudomonas spp. - M. Rajkumar; L. Benedict Bruno; J. Rajesh Banu (Critical Reviews in Environmental Science and Technology, 2017)

Predicting Irrigated and Rainfed Rice Yield Under Projected Climate Change Scenarios in the Eastern Region of India - A. V. M. Subba Rao; Arun K. Shanker; V. U. M. Rao; V. Narsimha Rao; A. K. Singh; Pragyan Kumari; C. B. Singh; Praveen Kumar Verma; P. Vijaya Kumar; B. Bapuji Rao; Rajkumar Dhakar; M. A. Sarath Chandran; et al. (Environmental Modeling & Assessment, 2016)

Rapid Diagnosis and Simultaneous Identification of Tuberculous and Bacterial Meningitis by a Newly Developed Duplex Polymerase Chain Reaction - Khushboo J. Nagdev; Sharda P. Bhagchandani; Shradha S. Bhullar; Rajkumar C. Kapgate; Rajpal S. Kashyap; Nitin H. Chandak; Hatim F. Daginawala; Hemant J. Purohit; Girdhar M. Taori (Indian Journal of Microbiology, 2015)

Tissue distribution of hepatopancreatic parvo‐like virus of shrimp in freshwater rice‐field crab, P aratelphusa hydrodomous ( H erbst) - N Madan; T Rajkumar; N Sundar Raj; M A Farook; K S N Nambi; S Abdul Majeed; A S Sahul Hameed (Journal of Fish Diseases, 2014)
An attempt was made to determine the replication efficiency of hepatopancreatic parvo‐like virus ( HPV ) of shrimp in different organs of freshwater rice‐field crab P aratelphusa hydrodomous ( H erbst) using bioassay, PCR , RT ‐ PCR , ELISA , Western blot and q‐ PCR analyses. Another attempt was made to use this crab as an alternative to penaeid shrimp for the large‐scale production of HPV . This crab was found to be highly susceptible to HPV by intramuscular injection. The systemic HPV infection was confirmed by PCR and W estern blot analyses in freshwater crab. The expression of capsid protein gene in different organs of infected crab was revealed by RT ‐ PCR analysis. Indirect ELISA was used to quantify the capsid protein in different organs of the crab. The copy number of HPV in different organs of the infected crab was quantified by q‐ PCR . The results revealed a steady decrease in C T values in different organs of the infected crab during the course of infection. The viral inoculum that was prepared from different organs of the infected crab caused significant mortality in post‐larvae of tiger prawn, P enaeus monodon ( F abricius). The results revealed that this rice‐field crab could be used as an alternative host for HPV replication and also for large‐scale production of HPV .

Fertility and apparent genetic anticipation in Lynch syndrome - Douglas Stupart; Aung Ko Win; Mark Jenkins; Ingrid M. Winship; Paul Goldberg; Rajkumar Ramesar (Familial Cancer, 2014)

Effect of a Previous Washing Step with Tannic Acid on the Quality of Minced Horse Mackerel ( Trachurus trachurus ) During Frozen Storage - Faisal Rashid Sofi; S. M. Zofair; Vijay Kumar Reddy Surasani; K. K. Sabha Nissar; Rajkumar Ratankumar Singh (Journal of Aquatic Food Product Technology, 2014)

Seasonality of the common cutworm Spodoptera litura in a soybean ecosystem - M. Punithavalli; A. N. Sharma; M. Balaji Rajkumar (Phytoparasitica, 2014)

Molecular mapping of genomic regions harbouring QTLs for root and yield traits in sorghum (Sorghum bicolor L. Moench) - Rajkumar; B. Fakrudin; S. P. Kavil; Y. Girma; S. S. Arun; D. Dadakhalandar; B. H. Gurusiddesh; A. M. Patil; M. Thudi; S. B. Bhairappanavar; Y. D. Narayana; P. U. Krishnaraj; et al. (Physiology and Molecular Biology of Plants, 2013)

Prospective biomarkers of stem cells of human endometrium and fallopian tube compared with bone marrow - S. Indumathi; R. Harikrishnan; J. S. Rajkumar; D. Sudarsanam; M. Dhanasekaran (Cell and Tissue Research, 2013)

Plasticity and banking potential of cultured adipose tissue derived mesenchymal stem cells - M. Dhanasekaran; S. Indumathi; R. Poojitha; A. Kanmani; J. S. Rajkumar; D. Sudarsanam (Cell and Tissue Banking, 2013)

Evaluating the effectiveness of conservation site networks under climate change: accounting for uncertainty - Robert Bagchi; Mike Crosby; Brian Huntley; David G. Hole; Stuart H. M. Butchart; Yvonne Collingham; Mohit Kalra; Jagadish Rajkumar; Asad Rahmani; Mitra Pandey; Hum Gurung; Le Trong Trai; et al. (Global Change Biology, 2013)
We forecasted potential impacts of climate change on the ability of a network of key sites for bird conservation (Important Bird Areas; IBA s) to provide suitable climate for 370 bird species of current conservation concern in two Asian biodiversity hotspots: the Eastern Himalaya and Lower Mekong. Comparable studies have largely not accounted for uncertainty, which may lead to inappropriate conclusions. We quantified the contribution of four sources of variation (choice of general circulation models, emission scenarios and species distribution modelling methods and variation in species distribution data) to uncertainty in forecasts and tested if our projections were robust to these uncertainties. Declines in the availability of suitable climate within the IBA network by 2100 were forecast as ‘extremely likely’ for 45% of species, whereas increases were projected for only 2%. Thus, we predict almost 24 times as many ‘losers’ as ‘winners’. However, for no species was suitable climate ‘extremely likely’ to be completely lost from the network. Considerable turnover (median = 43%, 95% CI = 35–69%) in species compositions of most IBA s were projected by 2100. Climatic conditions in 47% of IBA s were projected as ‘extremely likely’ to become suitable for fewer priority species. However, no IBA was forecast to become suitable for more species. Variation among General Circulation Models and Species Distribution Models contributed most to uncertainty among forecasts. This uncertainty precluded firm conclusions for 53% of species and IBA s because 95% confidence intervals included projections of no change. Considering this uncertainty, however, allows robust recommendations concerning the remaining species and IBA s. Overall, while the IBA network will continue to sustain bird conservation, climate change will modify which species each site will be suitable for. Thus, adaptive management of the network, including modified site conservation strategies and facilitating species' movement among sites, is critical to ensure effective future conservation.

Outcome definitions and clinical predictors influence pharmacogenetic associations between HTR3A gene polymorphisms and response to clozapine in patients with schizophrenia - A. P. Rajkumar; B. Poonkuzhali; A. Kuruvilla; A. Srivastava; M. Jacob; K. S. Jacob (Psychopharmacology, 2012)

Cytotoxicity of cyanide in primary culture of rat hepatocytes and its interaction with alpha-ketoglutarate - Rahul Bhattacharya; Janardhanan Hariharakrishnan; Ravindra M. Satpute; Rajkumar Tulsawani (Molecular & Cellular Toxicology, 2012)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

Photoluminescence Electron-Transfer Quenching of Rhenium(I) Complexes with Organic Sulfides - M. Rajkumar; J. Bhuvaneswari; M. Velayudham; E. Rajkumar; S. Rajagopal (Journal of Fluorescence, 2011)

New discovery of coral rubbings in the north-western Gulf of Kachchh, Gujarat, Western India — GIS based evaluation - J. Sesh Serebiah; M. Rajkumar; Jun Sun; B. A. Venmathi Maran; A. Saravanakumar; G. A. Thivakaran (Journal of Ocean University of China, 2011)

Polymorphism in the Prolactin Promoter and Its Association with Growth Traits in Chickens - T. K. Bhattacharya; R. N. Chatterjee; R. P. Sharma; M. Niranjan; U. Rajkumar; B. L. N. Reddy (Biochemical Genetics, 2011)

First record of three giant marine Bathynomids (Crustacea, Isopoda, Cirolanidae) from India - R. Sankar; M. Rajkumar; Jun Sun; A. Gopalakrishnan; T. M. Vasanthan; G. Ananthan; J. P. Trilles (Acta Oceanologica Sinica, 2011)

Bloom forming species of phytoplankton in two coastal waters in the Southeast coast of India - K. Thillai Rajasekar; M. Rajkumar; Jun Sun; V. Ashok Prabu; P. Perumal (Journal of Ocean University of China, 2010)

Seasonal variations of phytoplankton diversity in the Coleroon coastal waters, southeast coast of India - Rajasekar K. Thillai; M. Rajkumar; Jun Sun; Prabu V. Ashok; P. Perumal (Acta Oceanologica Sinica, 2010)

AFLP-Based Genetic Diversity Assessment of Commercially Important Tea Germplasm in India - R. K. Sharma; M. S. Negi; S. Sharma; P. Bhardwaj; R. Kumar; E. Bhattachrya; S. B. Tripathi; D. Vijayan; A. R. Baruah; S. C. Das; B. Bera; R. Rajkumar; et al. (Biochemical Genetics, 2010)

Influence of Silver Nanoparticles on 2,3-Bis(Chloromethyl)Anthracene-1,4,9,10-Tetraone - Mahalingam Umadevi; N. A. Sridevi; A. S. Sharmila; Beulah J. M. Rajkumar; M. Briget Mary; P. Vanelle; T. Terme; O. Khoumeri (Journal of Fluorescence, 2010)

Fishery resources in arid zone mangroves in gulf of Kachchh, Gujarat, northwest coast of India - A. Saravanakumar; M. Rajkumar; J. Sesh Serebiah; G. A. Thivakaran (Journal of Ocean University of China, 2009)

Fluorescence Quenching of 1,4-Dihydroxy-2,3-Dimethyl-9,10-Anthraquinone by Silver Nanoparticles: Size Effect - M. Umadevi; P. Vanelle; T. Terme; Beulah J. M. Rajkumar; V. Ramakrishnan (Journal of Fluorescence, 2009)

Spectral Investigations of Solvatochromism and Preferential Solvation on 1,4-Dihydroxy-2,3-Dimethyl-9,10-Anthraquinone - M. Umadevi; P. Vanelle; T. Terme; Beulah J.M. Rajkumar; V. Ramakrishnan (Journal of Fluorescence, 2008)

Molecular characterization of reciprocal crosses of Aerides vandarum and Vanda stangeana (Orchidaceae) at the protocorm stage - Rajkumar Kishor; H. S. Devi; K. Jeyaram; M. R. K. Singh (Plant Biotechnology Reports, 2008)

Molecular mapping of genomic regions harboring QTLs for stalk rot resistance in sorghum - P. Srinivasa Reddy; B. Fakrudin; Rajkumar; S. M. Punnuri; S. S. Arun; M. S. Kuruvinashetti; I. K. Das; N. Seetharama (Euphytica, 2008)

Benthic macrofaunal assemblage in the arid zone mangroves of gulf of Kachchh-Gujarat - A. Saravanakumar; J. Sesh Serebiah; G. A. Thivakaran; M. Rajkumar (Journal of Ocean University of China, 2007)

Identification of two RAPD markers genetically linked to a recessive allele of a Fusarium wilt resistance gene in pigeonpea (Cajanus cajan L. Millsp.) - H. Kotresh; B. Fakrudin; S. M. Punnuri; B. K. Rajkumar; M. Thudi; H. Paramesh; H. Lohithswa; M. S. Kuruvinashetti (Euphytica, 2006)

Characterization of a Novel Cr6+ Reducing Pseudomonas sp. with Plant Growth–Promoting Potential - M. Rajkumar; R. Nagendran; Kui Jae Lee; Wang Hyu Lee (Current Microbiology, 2005)

Diverse prevalence of large deletions within the OA1 gene in ocular albinism type 1 patients from Europe and North America - M. Bassi; Arthur Bergen; Pierre Bitoun; Stephen Charles; Maurizio Clementi; Richard Gosselin; Jane Hurst; Richard Lewis; Birgit Lorenz; Thomas Meitinger; Ludwine Messiaen; Rajkumar Ramesar; et al. (Human Genetics, 2001)